How interactional relationships matter for victim resistance during robberies: a video-observational analysis - Rosenkrantz Lindegaard, Marie (Criminological encounters, 2025)
Victims report resisting the offender’s demands in around four out of ten robberies. Yet so far, little research has examined how and why people perform such fearful and potentially dangerous resistance behaviors. Based on a qualitative analysis of video-captured shop robberies, we argue that victim resistance may be interpreted as a response to a violation of an interaction-ritualistic order: robbery victims resist and repair disruptions of this micro-social order, which are emotionally pleasing and a ground for everyday solidarities in the commercial setting. Adding to this interpretation, we find that resistance is disproportionally displayed by persons who had a face-to-face interaction with the primary robbery victim before the event and, as such, engaged in establishing an interactional relationship the moment the robbery started. We discuss theoretical implications, study limitations, and the prospect of using video-observational methods for the study of micro-interactional processes in robberies and beyond.